Government financial assistance to small and medium-sized enterprises in Malaysia - Hashim, Mohd Khairuddin; Zakaria, Mustafa; Hassan, Romle (UUM Press, 2011)
Small and medium-sized enterprises (SMEs) need adequate financial resources to sustain their business operations as well as to jnance their expansion programmes.The review of the small business literature indicates that financial constraints continue to be a major problem among the small firms, particularly in the Malaysian context. Despite the importance of financing SMEs, limited studies have attempted to examine the alternative sources of financing available to SMEs.This paper initiates an attempt to address this issue by highlighting the various government sources of financing available to Malaysian SMEs.